Trade Protection and the Role of Non-Tariff Barriers - Luisa Kinzius; Alexander-Nikolai Sandkamp; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2018)
A growing share of modern trade policy instruments is shaped by non-tariff barriers (NTBs). Based on a structural gravity equation and the recently updated Global Trade Alert database, we empirically investigate the effect of NTBs on imports. Our analysis reveals that the implementation of NTBs reduces imports of affected products by up to 12%. Their trade dampening effect is thus comparable to that of trade defence instruments such as anti-dumping duties. It is smaller for exporters that have a free trade agreement with the importing country. Different types of NTBs affect trade to a different extent. Finally, we investigate the effect of behind-the-border measures, showing that they significantly lower the importer's market access.
Keywords: F13; F14; 330; non-tariff barriers; trade protection; gravity equation